PARTISIPASI MASYARAKAT TERHADAP PEMBANGUNAN SUMBER DAYA MANUSIA DI DESA ONGKO KECAMATAN MAIWA KABUPATEN ENREKANG - Herman Dema; Andi Astinah; Yusmaeni Yusmaeni (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2020)
Abstract The Effect of Community Participation on Human Resource Development in Ongko Village, Maiwa District, Enrekang Regency. Muhammadiyah Sidenreng Rappang University. The aim of this study; 1) to find out community participation in Ongko Village,2) to know the development of Human Resources in Ongko Village, 3) to determine the effect of community participation on Human Resource Development in Ongko Village, The research location was Ongko Village, The study was conducted for two months, starting March-May 2019. The population in this study was 267 families. The sampling technique uses simple random sampling technique and uses the Slovin formula so that the sample in this study amounted to 73 households. Data collection techniques using observation, questionnaires, interviews and literature studies. Quantitative data analysis techniques used are frequency tabulation analysis and simple regression analysis. The results showed that; 1) results of community participation of 70% included in the category of "good", 2) results of the development of Human Resources amounting to 76.8% which included the category of "good", 3) the effect of community participation on the development of Human Resources in Ongko Vilage is significant where the value of t arithmetic = 6,750> t table = 2,646 with a significance value of 0,000 <0.05. It can be said that the better the community participation, the more the development of Human Resources in Ongko Village, so that Ho is rejected H1 accepted.